Freshwater sample preservation for the analysis of dissolved low molecular mass thiols. (19th September 2017) - Leclerc, Maxime; Planas, Dolors; Amyot, Marc
Abstract: Low molecular mass (LMM) thiols are ubiquitous organosulfur peptides that play key roles in biogeochemical element cycling. These LMM thiols, found at low concentrations in the water column, are highly sensitive to oxidation and degradation processes which may lead to problems with detection and analysis. Natural water samples should be stored and handled appropriately to reduce thiol loss in the time period from sampling to analysis. Storage temperatures were investigated for optimal preservation of four thiols species. Thiol degradation varied between species and was generally slower in samples stored at −80°C and 4°C compared to −20°C and 21°C. Two natural freshwater matrices were tested, one from a fluvial lake subject to agricultural inputs and one from an oligotrophic pristine lake. After 6 d of storage at −20°C, the most affected thiol species was glutathione with a degradation rate ( k D ) of (3.0 ± 0.5) × 10 −3 h −1 in the fluvial lake water andl ‐cysteine‐l ‐glycine (CYS‐GLY) with a k D of (3.8 ± 0.8) × 10 −3 h −1 in the oligotrophic lake water. Argon purging of samples did not prevent thiol degradation or oxidation after storage for 7 d. Pre‐concentration by freeze‐drying techniques led to significant loss for every thiol species tested (up to 65% for cysteine). We recommend improving storage methods by using temperatures of −80°C or 4°C. The use of correction factors to estimate initial thiol concentrations is possible but should be used with caution due to highly site‐specific k D in natural waters.